2007
DOI: 10.1576/toag.9.2.088.27309
|View full text |Cite
|
Sign up to set email alerts
|

Uterine leiomyosarcomas: a review of the diagnostic and therapeutic pitfalls

Abstract: Key content Uterine leiomyosarcomas are the most common uterine sarcoma and they are notoriously aggressive in nature. Preoperative diagnosis is difficult and they are usually detected as an incidental finding at surgery. Tumour stage is the most important prognostic factor. Misdiagnosis or delay in diagnosis can occur following the use of conservative techniques for managing uterine fibroids. The primary treatment is surgical, while the role of adjuvant therapy is still to be clearly defined. Learning obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 58 publications
0
35
0
3
Order By: Relevance
“…Pathologic diagnosis through endometrial biopsy is unreliable, with sensitivity of only 30% because a low number of tumors have contact with the uterine cavity. 6 Transcervical needle biopsy for findings suggestive of uterine tumors navigated by ultrasound or magnetic resonance imaging is a possible diagnostic alternative. 6 Tamura et al 27 Performing minimally invasive surgery or using morcellation to remove myomas is not recommended if the preoperative examination findings are suggestive of uterine malignancy because it is known that the dissemination of malignant tumor cells in the abdominal cavity is associated with worsening of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathologic diagnosis through endometrial biopsy is unreliable, with sensitivity of only 30% because a low number of tumors have contact with the uterine cavity. 6 Transcervical needle biopsy for findings suggestive of uterine tumors navigated by ultrasound or magnetic resonance imaging is a possible diagnostic alternative. 6 Tamura et al 27 Performing minimally invasive surgery or using morcellation to remove myomas is not recommended if the preoperative examination findings are suggestive of uterine malignancy because it is known that the dissemination of malignant tumor cells in the abdominal cavity is associated with worsening of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…6 Transcervical needle biopsy for findings suggestive of uterine tumors navigated by ultrasound or magnetic resonance imaging is a possible diagnostic alternative. 6 Tamura et al 27 Performing minimally invasive surgery or using morcellation to remove myomas is not recommended if the preoperative examination findings are suggestive of uterine malignancy because it is known that the dissemination of malignant tumor cells in the abdominal cavity is associated with worsening of the disease. 28 A shorter disease-free interval, reduced overall survival rate, and a higher risk of recurrence have been demonstrated in cases of morcellation of uterine sarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recommended that aggressive surgical cytoreduction at the time of initial diagnosis offers the best possibility of prolonged survival (11,12). The role of adjuvant therapies have been investigated over the last decades, however, as many of the studies are underpowered with conflicting reports, there have been no randomized controlled trial (RCT) to date that have unambiguously demonstrated improved overall survival when using adjuvant radiotherapy or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The need of the hour is not to panic and abandon the procedure but follow certain guidelines. They are: (A) Do a good preoperative workup to rule out any carcinomatous changes, (B) informed consent, (C) Gd-DTPA enhanced MRI along with LDH3 isoenzyme measurements gives promising results to differentiate leiomyoma from leiomyosarcoma, 7 (D) vaginal morcellation better than abdominal morcellation whenever possible and (E) use of endobags during morcellation to prevent spillage and dissemination of the specimen.…”
Section: Discussionmentioning
confidence: 99%